Resistance training in football - Kalinowski, Paweł; Sysiak, Wojciech; Jerszyński, Damian; Gronek, Piotr (Akademia Wychowania Fizycznego w Poznaniu)
Among the methods that can improve football players’ motor skills, resistance training plays an important role, being one of the components of functional training in which players use their own body weight in all planes of movement. Currently in football, refining motor skills takes place on many levels, for instance, through resistance training. Optimal performance of a specific motor pattern and development of specific dominants such as stability, mobility and neuromuscular coordination increases the chance of improving the level of fitness. While discussing the importance of soccer training, attention was paid to the specific nature of work performed as well as the intensity and volume of applied effort during the broadly understood training process in football. In the aspect of developing motor skills, the role of functional loads in resistance training was emphasized which has a beneficial effect on improving speed, strength, coordination and endurance in football.